Kontaminasi Soil Transmitted Helminths (STH) pada Daun Bawang (Allium fistulosum L.) - Dwi Ratna Cahyaningrum; Ririh Jatmi Wikandari (Poltekkes Kemenkes Semarang, 2022)
Soil Transmitted Helminths (STH) infection is still a health problem in Indonesia. This infection is caused by intestinal nematodes which in its transmission require soil media. Vegetables can be a medium of transmission of STH. STH transmission occurs when the soil is contaminated with STH worm eggs and the worm eggs stick to vegetables. In addition, STH contamination can occur in traditional markets with poor sanitation such as humid rooms, floors with lots of puddles, muddy water, and improper placement of waste. The aim of the study was to describe the contamination of Soil Transmitted Helminths on Scallion (Allium fistulosum L.). This research is a descriptive research, the examination of worm eggs is done by indirect method with sedimentation technique. The research sample was taken from 25 traders. Leeks contaminated with STH as many as 15 (60%) samples from 25 traders. The type of STH found was hookworm rhabditiform larvae. There is STH contamination in leeks sold at the Bangetayu market, Semarang City. To avoid the risk of being infected with STH, people are expected to consume vegetables that have been cooked.